URGENSI PENDIDIKAN ANTI KORUPSI BAGI GENERASI MUDA DALAM MENCAPAI INDONESIA BEBAS KORUPSI - Julpan Hartono SM Manurung; Asnur Disyahputra; Ari Dermawan; Kharina Chandra Wani Sinaga (Smart Education, 2025)
Abstract: Abstract: The state has the responsibility for education for its citizens, this responsibility has been regulated in the 1945 Constitution and Law Number 20 of 2003 concerning the National Education System. The word corruption comes from the Latin corruptio or corruptus. Corruptio has various meanings, namely the act of damaging or destroying. Corruptio is also interpreted as rottenness, ugliness, depravity, dishonesty, can be bribed, immoral, deviation from holiness, words or statements that insult or slander. The problems are: The Urgency of Anti-Corruption Education for the Younger Generation in Achieving a Corruption-Free Indonesia. Challenges in Anti-Corruption Education for the Younger Generation. Corruption is part of the type of crime that can affect various interests concerning human rights, state ideology, economy, state finances, national morals, and so on, it is a criminal behavior that is difficult to overcome. This problem greatly hinders national development and is detrimental to state finances. If this problem occurs continuously, it can eliminate the sense of justice and trust in the law and regulations by the community. Anti-corruption education will be implemented at all levels of education starting from the 2012/2013 academic year. The challenge in implementing Anti-Corruption Education in preventing criminal acts is of course in terms of not yet being a mandatory subject of Anti-Corruption Education (PAK) in Higher Education. Another obstacle is the absence of special TOT training actively and integrated for lecturers in Indonesia, who are truly focused on the anti-corruption movement. Keywords: Education, Corruption, Young Generation Abstrak: Negara mempunyai taggung jawab atas Pendidikan bagi warga negaranya, tanggungjawab tersebut sudah diatur dalam Undang-Undang Dasar 1945 dan Undang-Undang Nomor 20 tahun 2003 tentang Sistem Pendidikan Nasional. Kata korupsi berasal dari bahasa latin corruptio atau corruptus. Corruptio memiliki arti beragam yakni tindakan merusak atau menghancurkan. Corruptio juga diartikan kebusukan, keburukan, kebejatan, ketidakjujuran, dapat disuap, tidak bermoral, penyimpangan dari kesucian, kata-kata atau ucapan yang menghina atau memfitnah. Adapun menjadi permasalah yaitu : Urgensi Pendidikan Anti Korupsi Bagi Generasi Muda Dalam Mencapai Indonesia Bebas Korupsi.Tantangan dalam Pendidikan Anti Korupsi Bagi Generasi Muda.Tindak pidana korupsi menjadi bagian dari jenis kejahatan yang dapat mempengaruhi berbagai kepentingan yang menyangkut hak asasi, ideologi negara, perekonomian, keuangan negara, moral bangsa, dan sebagainya, hal itu merupakan perilaku jahat yang sulit di tanggulangi. Pendidikan Antikorupsi akan diberlakukan di seluruh jenjang pendidikan mulai tahun ajaran 2012/2013. Tantangan dalam Penerapan Pendidikan Anti Korupsi dalam mencegah Tindak Pidana tentu dalam hal belum menjadi mata kuliah wajib Pendidikan Anti Korupsi (PAK) di Perguruan Tinggi. Kendala lain belum adanya pelatihan khusus TOT secara aktif dan terapdu terhadap dosen di Indonesia, yang benar-benar fokus dalam gerakan antikorupsi. Kata kunci: Pendndikan,Korupsi, Generasi Muda